Nonmosaic 45, XO karyotype in a woman with Turner syndrome without any cognitive, psychosocial or behavioral deficiencies (A Case report) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
A 22 year old woman with primary amenorrhea came to The Reproductive Endocrinology and Infertility Centre, University of Gadjah Mada, Dr.Sardjito Hospital. She had no abnormalities in cognitive, psychosocial or behavioral capacities, she had almost completed her university degree. On examination she had no secondary sexual development, no pathognomonic abnormal phenotype related to abnormal karyotype. There was no indication of family history associated ,